Spined Soldier Bug, Podisus maculiventris (Say) (Insecta: Hemiptera: Pentatomidae) - David B. Richman; Frank W. Mead (EDIS)
This document is EENY-231, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2001.